Beyond performance and protocols: early responders' experiences of multiple accountability demands in the response to the 2015 Nepal earthquake. Issue 1 (27th May 2020) - Dhungana, Nimesh; Cornish, Flora
Abstract : Critics have long questioned the push for professionalised and performance‐driven accountability in the humanitarian sector, yet the matter is largely treated as a 'back office' issue of standards, guidelines, and processes. Scant attention is paid to the accountability demands experienced by early responders to disasters. Set in the contested climate of the emergency response to the earthquake in Nepal on 25 April 2015, and drawing on interviews with 15 early responders, this paper reveals three forms of accountability demands: (i) accountability as compliance; (ii) accountability as the object of government regulation; and (iii) accountability as public opposition and interrogation. Beyond the performance‐centric, non‐governmental organisation‐driven understanding of accountability, early responders to the earthquake experienced multidirectional accountability demands, not only from donors and beneficiaries, but also from the national government and wider public. Engaging with public criticism is a significant feature of early responders' responsibility that warrants further consideration by the humanitarian community.